Ecological aspects of influence of solid domestic wastes in agricultural landscapes, water environment and atmospherе air - Молчанова, А. В. (Scientific Progress & Innovations, 2016)
In terms of economic restructuring of Ukraine, new ways, methods and forms of management leads to a growing number of modern industrial and food for the population and, consequently, the growth of solid waste. In the development of human civilization inevitably turns our planet into a huge trash, and nature has no mechanisms of recycling and disposal of waste produced by society because last one accumulates in the biosphere exponentially. Currently, the issue of waste management is next to the environmental pollution from chemical and biological components that are constantly present in them, as well as the protection of public health, which are in the zone of their direct or indirect influence. The problem of waste is a key environmental issues, and all more significant in terms of resource. Landfill – a typical example of human activities. They are characterized by a number of signs of chemical contamination of soil, surface water, soil and groundwater, plant groups of air that are the subject of various environmental studies.